Membaca Ulang Kejadian 26:12-13: Sebuah Kritik Hermeneutis terhadap Prosperity Gospel (Jurnal Riset Rumpun Agama dan Filsafat, 2026)
This study reexamines Genesis 26:12–13 to illuminate the hermeneutical tension between the original meaning of the Hebrew term זָרַע (zāraʿ) and the interpretive patterns characteristic of the Prosperity Gospel. Through a historical-critical approach combined with narrative analysis, the study demonstrates that Isaac’s act of sowing must be understood as an actual agrarian activity undertaken within conditions of crisis and limitation, and grounded in the initiative and faithfulness of God. The findings indicate that the blessing Isaac received was never intended as a universal, reproducible formula but as a theological declaration of divine care within a history marked by uncertainty. In contrast, the Prosperity Gospel employs a hermeneutic that is predominantly literal and selective in its use of texts while disregarding their contexts, thereby reshaping the covenant narrative into a reductive pattern of guaranteed prosperity. This analysis shows that such reading not only shifts the theological focus of the text but also obscures the dynamics of faith, obedience, and grace that form the heart of the narrative. The study affirms the necessity of a more critical and responsible hermeneutic and argues that recovering the historical context and narrative structure serves as an essential theological corrective to Prosperity Gospel readings that detach the text from its original context.